Self-Perception of Parental Role, Family Functioning, and Familistic Beliefs in Italian Parents: Early Evidence - Delvecchio, Elisa; Di Riso, Daniela; Salcuni, Silvia (Frontiers in Psychology, 2016)
Recent research has explored the relationships between family and cultural issues, claiming attention on the need to consider and evaluate cultural values and beliefs as useful factors to promote positive family adjustment and parenting outcomes (Cardoso and Thompson, 2010; Taylor, et al., 2012). This paper explored self-perception of parental role, family maladjustment and cultural beliefs in a sample of Italian parents. More specifically, 204 mother and 204 fathers of adolescents (13 to 17 years old) filled self-report questionnaires about family system maladjustment (Family Assessment Measure-III), self-perception of parental role (Self-Perception of Parental Role), parents’ beliefs and attitudes toward the family (Attitudinal Familism Scale), and parents’ cultural values (Cultural Values Survey). Results showed that parents have a similar self-perception of family functioning and they share common cultural beliefs and values toward the family. However, fathers felt more satisfied and involved in parenting then mothers and they were more able to balance the different roles of their life. Mothers and fathers showed a similar path of correlations, in which greater level of satisfaction in parenting and better ability in role balancing correlated with a more positive family adjustment. Moreover, a higher perception of family maladjustment was associated to lower levels of family cohesion and cooperation. Furthermore, higher levels of satisfaction were associated to higher scores in family solidarity, equality among sexes and equality in decision takers. These results introduce important implications for family studies in Italian culture, and open to comparison with parenting in other cultures.